Effective Stress-Based Numerical Method for Predicting Large-Diameter Monopile Response to Various Lateral Cyclic Loadings - Jichao Lei; Kehua Leng; Wei Xu; Lixian Wang; Yu Hu; Zhen Liu (Journal of Marine Science and Engineering)
Extreme marine environmental cyclic loading significantly affects the serviceability of monopiles applied for the foundation of offshore wind turbines (OWTs). Existing research has primarily used p-y methods or total stress-based models to investigate the behavior of monopile–marine clay systems, overlooking the pore pressure development in subsea clay. Studies on the effective stress-based behavior of clay under various lateral cyclic loading conditions are limited. This paper presents an effective stress-based 3D finite element numerical method developed to predict key behaviors of pile–clay systems, including permanent pile rotation under cyclic loading, pile bending moment, and the evolution of pore pressure in subsea clay. The model is verified by contrasting the simulations results to centrifuge experimental results. Cyclic lateral loading is divided into average cyclic load and amplitude of cyclic load to investigate their impacts on the pile–clay system response. The research findings offer insights for the design of large-diameter monopiles under complex cyclic loading conditions.